The Impact of Real Find Object Game To Enrich Students’ Vocabulary Mastery - Virna Kris Angelina (CV. Arunika Media Nusantara, 2025)
This research is motivated by the low vocabulary mastery of students at SMP Negeri 2 Tobadak which is caused by the lack of student learning motivation in enriching new vocabulary in English. The purpose of this study was to determine whether the use of Real Find Object Game can improve the English vocabulary mastery of eighth grade students and how it impacts students' learning motivation after learning using Real Find Object Game. This study used a quantitative approach with a quasi- experimental design involving two classes, namely the experimental class VIII A and the control class VIII B. The population consisted of all students of SMP Negeri 2 Tobadak, with a sample of 32 students selected using random sampling techniques. Data collection instruments used tests, including: pre-test and post-test to measure the increase in students' vocabulary mastery and questionnaires to obtain information about students' motivation. Data were analyzed using SPSS. The results of this study showed that it was successful in improving students' vocabulary mastery as seen from the average post-test score of the experimental class, which was 87.19, higher than the average pre-test score, which was 41.25. The results of the paired sample t-test showed a significance value (2-tailed) of 0.000 <0.05, which indicated that H0 was rejected and H1 was accepted. In addition, students' intrinsic and extrinsic motivation increased higher after using Real Find Object Game. Object Game with an overall sub-indicator score: intrinsic motivation 86.25% (very high), extrinsic 85% (very high). Therefore, it can be concluded that the use of the Real Find Object Game application in learning English vocabulary, especially nouns, is effective in enriching students' vocabulary mastery. From this study, English teachers can adopt this game-based learning method as an alternative to overcome the problem of lack of student motivation.